PENDIDIKAN ISLAM DALAM PERSPEKTIF FILSAFAT ILMU - Zainal Arifin (Ta'dib: Jurnal Pendidikan Islam, 2014)
There are some problems in Islamic education either theoretically or practically. Based on its theoretical problem, it have not been definite the ontological Islamic education source and there was a dichotomy in Islamic education epistemology which is caused the separation of religion science and general science. Based on its practical problem, there was some moral degradation of the students in some Islamic institutions. This article describes the Islamic education analysis based on philosophical science perspective (ontology, epistemology, and axiology) and describes the solutions from those problems.There were some conclusions taken from the description above; 1) based on Islamic education ontological theory, there are two kinds of science as they are material substance science and non-material substance science. 2) based on Islamic education epistemological theory, there are two kinds of science as they are kasbi science and ladunni science. 3) based on Islamic education axiological theory, there are two functions of science as they are beneficial for human being in real life and after life.